Nothing to lose: Processing blindness to potential losses drives thrill and adventure seekers - Kruschwitz, Johann D. (2011)
Sensation seeking has been linked to increased risk taking and is therefore crucial in influencing behavioral outcomes of risk-taking behavior. Using functional magnetic resonance imaging (fMRI), the neural underpinnings of risk appraisal were studied in a large subject sample (n=188), stratified according to thrill and adventure seeking (TAS) ratings. As defined by a median split of the sample, low and high TAS groups were compared on a simple decision-making task completed during fMRI. The task was designed such that risk (i.e., magnitude of outcome) and gains (i.e., direction of outcome) could be mapped independently. Behavioral analysis indicated that high TAS individuals are more sensitive to rewards but less discriminating between risk with and without punishment and that low TAS individuals are less sensitive to rewards but quite sensitive to receiving punishments in risky situations. Imaging results on the group differences for the interaction between level of risk and level of gain showed differences in the right superior frontal gyrus (BA6), left insula (BA21), right nucleus accumbens, left lentiform nucleus, and left precuneus (BA7). The presented data suggest a neural model of risk processing in sensation seeking individuals such that the positive response to reward outweighs the impact of equivalent loss. This imbalance in approach/avoidance is evident in differences in the underlying neural substrates in TAS individuals and leads to greater risk behavior in the face of potential loss.